Optimizing Social Media Utilization and Parental Involvement to Enhance the Quality of Basic Education Services in Beji District, Pasuruan - Heri Priyanto; Ahmad Thohirin; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was motivated by the importance of improving the quality of educational services in elementary schools as a key indicator of successful educational management. In the digital era, schools' use of social media and parental support are considered important factors that may contribute to enhancing the quality of educational services. This study aims to examine the effect of social media utilization on the quality of educational services, the effect of parental support on the quality of educational services, and the simultaneous effect of social media utilization and parental support on the quality of educational services in public and private elementary schools in Beji District, Pasuruan Regency. The study employed a quantitative approach using a correlational research design. Data were collected through questionnaires administered to 77 respondents, consisting of teachers and school principals from public and private elementary schools in Beji District. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination with the assistance of SPSS software. The findings indicate that social media utilization has a positive and significant effect on the quality of educational services. Parental support also has a positive and significant effect on the quality of educational services. Furthermore, the simultaneous influence of social media utilization and parental support significantly improves the quality of educational services. These findings support the SERVQUAL model, Social Support Theory, and the concept of communication technology utilization in education, all of which emphasize the importance of effective communication, collaboration, and stakeholder participation in improving educational service quality. This study implies that optimizing the use of social media and strengthening parental involvement are essential strategies for enhancing the quality of educational services in elementary schools. Future studies are recommended to expand the research area, increase the number of respondents, and examine additional variables that may influence the quality of educational services.